Hyperhidrosis: causes and treatment options - Olga Jabłonowska; Anna Woźniacka; Bożena Dziankowska-Bartkowiak (Termedia Publishing House, 2020)
Excessive sweating (hyperhidrosis) is a common condition developing regardless of age, sex, and race, which often leads to a decrease in the quality of life. Depending on the cause, hyperhidrosis can be divided into the primary and secondary type (triggered by comorbidities, drugs, stress). Based on the degree of body involvement, hyperhidrosis may be either focal or generalised. Primary hyperhidrosis limited to certain body areas accounts for a vast majority of cases. According to the Canadian Hyperhidrosis Advisory Committee primary hyperhidrosis can be diagnosed if the symptoms persist for at least 6 months, and at least 4 of the following 6 criteria are fulfilled: bilaterally symmetric sweating, impairment of daily activities, more than 1 episode per week, age at onset < 25 years, positive family history, and absence of symptoms during sleep. First-line therapy of primary hyperhidrosis is based on topical medications. If no improvement is noted, systemic or surgical options are considered (e.g. iontophoresis, botulin toxin injections). In secondary hyperhidrosis, the focus is on the treatment of the underlying cause.